2012
DOI: 10.1074/mcp.r111.013037
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Control or Oxidative Damage? Proteomic Approaches to Interrogate the Role of Cysteine Oxidation Status in Biological Processes

Abstract: Oxidation is a double-edged sword for cellular processes and its role in normal physiology, cancer and aging remains only partially understood. Although oxidative stress may disrupt biological function, oxidation-reduction (redox) reactions in a cell are often tightly regulated and play essential physiological roles. Cysteines lie at the interface between these extremes since the chemical properties that make specific thiols exquisitely redox-sensitive also predispose them to oxidative damage by reactive oxyge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
98
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(100 citation statements)
references
References 121 publications
0
98
0
2
Order By: Relevance
“…Also, the previous SRM analysis of mitochondria from P. anserina showed that the examined oxidative modification in the ATP synthase subunit alpha remained rather unaffected by aging (42). These recent findings suggest that ROS level is wellcontrolled during aging and functionally regulates essential physiological processes in the cell (79,80). For this purpose, pathways for special ROS signaling seem to exist which regulate also ROS homeostasis for alleviating the toxicity of ROS (2).…”
Section: Can Previous Studies On Oxidative Damage and Protein Abundanmentioning
confidence: 87%
“…Also, the previous SRM analysis of mitochondria from P. anserina showed that the examined oxidative modification in the ATP synthase subunit alpha remained rather unaffected by aging (42). These recent findings suggest that ROS level is wellcontrolled during aging and functionally regulates essential physiological processes in the cell (79,80). For this purpose, pathways for special ROS signaling seem to exist which regulate also ROS homeostasis for alleviating the toxicity of ROS (2).…”
Section: Can Previous Studies On Oxidative Damage and Protein Abundanmentioning
confidence: 87%
“…Second, oxidized cysteines are expected to be more than an order of magnitude less present when compared with reduced cysteines in highly reducing cell compartments such as the bacterial cytoplasm. Because of the limited dynamic range of an MS-based quantitation, some oxidized cysteines can remain undetected (40). Third, overoxidized, irreversibly modified cysteines will escape our analysis.…”
Section: Discussionmentioning
confidence: 99%
“…This is the case of trapping reduced thiols (-SH) with permeable alkylating agents such as maleimide derivatives, or sulfenic acid (-SOH) with membrane diffusible dimedone derivatives (see below). Alternatively, the redox state of the cell is mainly preserved by "freezing" thiols and decreasing thiol reactivity with acids such as trichloroacetic acid (TCA) added to cell cultures, which rapidly protonates all redox-active thiolate anions by shifting the pH below their pKa, and also stops thiol-disulfide exchanges by precipitating and denaturing proteins (40,59). Later on extract preparation, thiol reactive probes (i.e.…”
Section: Principles For the Characterization Of The Redox Status Of Pmentioning
confidence: 99%